Osteosynthesis of consolidated jaw fracture - Rodrigues Godinho, Ana Bárbara; Sofal , Luiz Cláudio; de Moraes Souza, Aline Luize; da Silva Correa Linck, Isabel Cristina (Pubvet, 2021)
Mandibular fractures are common in small animal surgery and their relevance is directly linked to the functional importance of this bone. They usually result from injuries resulting from being run over, falling, and fighting, with the highest incidence between the first premolar and the second molar. The goal of treating jaw fractures will be to return to normal function with perfect or satisfactory dental occlusion so that the animal can return to eating normally. At the veterinary clinic Zoodonto, a canine species, female, SRD, with three years of age, weighing 18.4 kg, presenting dental malocclusion due to consolidated bilateral fracture of the mandible body, between the 1st and 2nd lower molars between the 1st and 2nd left lower premolars. The surgical technique used was a fracture of bone calluses with chisel and hammer, repositioning of the jaw, and fixation with steel wire using the non-invasive technique of bonding and acrylic resin bisacrylate. Knowledge of the type, frequency, and therapies used in mandibular fractures is of fundamental importance for a veterinary clinic. It is necessary to improve the techniques for fixing, correcting, and stabilizing fractures that occur with a greater incidence, thus increasing efficiency in their treatment and not only the investment in research of new materials and technologies that overcome the limitations of therapeutic models. In this sense, this work aims to report a case of mandibular fracture in which the technique of tying up culminated in an adequate bone stabilization and consolidation.
Keywords: Dog; consolidation; occlusion